Liposuction in gynecomastia: an institutional experience - Rayamajhi, Jyoti; Rawal, Sushil; Malla, Srijan (Medical Journal of Shree Birendra Hospital, 2017)
Introduction: Gynecomastia is a benign condition of the male breast with glandular tissue proliferation. It can be physiologic or pathologic and many a times manifestation off underlying chronic pathology. Its treatment is selected based on cause, age and grade with surgical or pharmacological modalities. Periareolar incision with liposuction is the choice for higher grade gynecomastia.Methods: Patients record of Gynecomastia undergoing surgery for last two years from a tertiary hospital was reviewed retrospectively. Detail clinical evaluation and appropriate investigations obtained from medical records. Patients with chronic liver and renal disease, hyperthyroidism, alcoholics and patients on medical treatment as anabolic steroids were excluded from the study. Treatment of gynecomastia and its outcome was recorded and entered in excel and analyzed.Results: Among 33 patients enrolled, nineteen had unilateral gynecomastia whereas 14 patients had bilateral gynecomastia. Of them 10 were of Simons grade I, 17; IIA and 6; of IIB. Among operated patients mean age was 53.24 years.Conclusions: Periareolar incision with liposuction is the treatment of patient choice for higher gynecomastia due to its better outcome in terms of complication and patient satisfaction.